2020
DOI: 10.3390/v12010098
|View full text |Cite
|
Sign up to set email alerts
|

Distinct MCM10 Proteasomal Degradation Profiles by Primate Lentiviruses Vpr Proteins

Abstract: Viral protein R (Vpr) is an accessory protein found in various primate lentiviruses, including human immunodeficiency viruses type 1 and 2 (HIV-1 and HIV-2) as well as simian immunodeficiency viruses (SIVs). Vpr modulates many processes during viral lifecycle via interaction with several of cellular targets. Previous studies showed that HIV-1 Vpr strengthened degradation of Mini-chromosome Maintenance Protein10 (MCM10) by manipulating DCAF1-Cul4-E3 ligase in proteasome-dependent pathway. However, whether Vpr f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…We additionally demonstrated that the Vpr cell cycle arrest null mutant R80A fails to suppress degradation of CCDC137 a finding that also agrees with previous proteomic results (Greenwood et al, 2019), in which depletion of CCDC137 in the presence of cell cycle null mutant S79A was similar to that observed for WT Vpr. We found that siRNA depletion of CCDC137 did not induce cell cycle arrest whereas depleting MCM10 by the same method did lead to G2/M cell cycle arrest, as expected (Chang et al, 2020;Chattopadhyay and Bielinsky, 2007;Romani et al, 2015). Consistent with this result, CCDC137 depletion did not induce inhibitory phosphorylation of CDK1 at Y15, which is a requirement for arrest at the G2/M boundary (Jin et al, 1996).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We additionally demonstrated that the Vpr cell cycle arrest null mutant R80A fails to suppress degradation of CCDC137 a finding that also agrees with previous proteomic results (Greenwood et al, 2019), in which depletion of CCDC137 in the presence of cell cycle null mutant S79A was similar to that observed for WT Vpr. We found that siRNA depletion of CCDC137 did not induce cell cycle arrest whereas depleting MCM10 by the same method did lead to G2/M cell cycle arrest, as expected (Chang et al, 2020;Chattopadhyay and Bielinsky, 2007;Romani et al, 2015). Consistent with this result, CCDC137 depletion did not induce inhibitory phosphorylation of CDK1 at Y15, which is a requirement for arrest at the G2/M boundary (Jin et al, 1996).…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies demonstrated that depletion of CCDC137 in 293FT or U2OS results in G2/M cell cycle arrest (Zhang and Bieniasz, 2020) and we sought to reproduce this phenotype. We included minichromosome maintenance 10 replication initiation factor (MCM10) as a positive control since MCM10 degradation has been clearly shown to be enhanced by Vpr and to induce cell cycle arrest in multiple reports (Chang et al, 2020;Chattopadhyay and Bielinsky, 2007;Romani et al, 2015). To determine whether CCDC137 depletion results in G2/M cell cycle arrest, HeLa cells were transfected with either a control, non-specific scrambled siRNA or CCDC137 or MCM10 siRNAs.…”
Section: Depletion Of Ccdc137 In Hela Cells Using Sirna Does Not Results In G2/m Cell Cycle Arrestmentioning
confidence: 99%
“…Previous studies have demonstrated the expression of Vpr-binding proteins, including DCAF1, SAP145, p300, SLX4, importin α, and MCM10 in cells other than MDMs [18,19,27,29,[38][39][40][41]. In this study, we identified the novel Vpr-binding proteins PRMT5 and PRMT7.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, Vpr has the potential to increase virus production in cells of the monocyte-macrophage lineage and in a subtype of CD4 + T cells [31][32][33][34][35][36][37]. Vpr carries out its functions through interactions with various host factors, such as DDB1-and CUL4-associated factor 1 (DCAF1), spliceosome-associated protein 145 (SAP145), p300, synthetic lethal of unknown (X) function 4 (SLX4), importin α, and mini-chromosome maintenance protein10 (MCM10) [18,19,27,29,[38][39][40][41]. Although, Vpr function is important for HIV-1 pathogenesis in macrophages, the specific mechanisms of Vpr in this context are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Vpr is an accessory gene product of the human immunodeficiency virus type 1 (HIV-1) and a small 15-kDa protein with multiple biological functions, including splicing regulation [1][2][3], support of virus release [4], nuclear import of the viral preintegration complex in macrophages [5][6][7], enhanced expression and processing of the envelope glycoprotein in macrophages [8][9][10], sustaining interleukin 6 expression to enhance HIV-1 replication [11], antagonism of exonuclease 1-and helicase-like transcription factor-mediated restriction in T cells through degradation of these proteins [12][13][14][15], regulation of apoptosis in both a positive and negative manner, and the induction of cell cycle arrest at the G2 phase in dividing cells [16][17][18][19][20][21]. Multiple functions of Vpr are exerted through interactions with various host factors, such as DNA damage-binding protein 1 (DDB1)-and cullin 4 (CUL4)-associated factor 1 (DCAF1), spliceosome-associated protein 145, p300, synthetic lethal of unknown (X) function 4 (SLX4), protein arginine N-methyltransferase 5, importin α, mini-chromosome maintenance protein10, and coiled-coil domain-containing-137 (CCDC137) [2,6,7,13,20,[22][23][24][25][26][27]. The induction of G2 arrest is likely an important function for efficient viral replication because the ability of Vpr to cause cell cycle blockade is well conserved among primate lentiviruses [28,29].…”
Section: Introductionmentioning
confidence: 99%